God is king : understanding an Israelite metaphor - Brettler, Marc Zvi (Journal for the study of the Old Testament. Supplement series ;, 1989)
This is the first attempt in biblical studies to apply the tools developed by theoreticians of metaphor to the common biblical metaphor of God as king. The extent to which elements of human kingship are projected onto God is investigated, and several significant conclusions emerge: 1. Royal characteristics that have a diminutive connotation are generally not projected onto God. 2. God's nature as greatest king is emphasized through use of superlatives. For example, his garb is enormous and he has a large number of royal attendants. God is not limited by the metaphor. 3. When the entailments of.